Assessment of Functional Outcome Following Duhamel Retro-Rectal Pull-Through Surgery for Hirschsprung's Disease - A Follow-up Study - Raghunath S. M.; Raghul Maniam; Vembar Dhanasekarapandian; Hariharan Govindarajan (Journal of Coloproctology, 2023)
Context Hirschsprung's disease (HD) is one of the commonest problems requiring surgery in children. More than 95% of children present during new-born period, when they are treated with leveling colostomy and are followed with pull-through surgery a few months later, once the child has gained adequate weight to withstand a major surgery. The commonest pull through surgery done is the Duhamel retro-rectal pull-through (DRPT) repair.